2015
DOI: 10.1016/j.foreco.2015.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clear-felling versus gradual removal of conifer trees on the survival of understorey plants during the restoration of ancient woodlands

Abstract: a b s t r a c tPlantations of exotic conifers on ancient woodland sites retain many features of high conservation value and in many countries such sites are being actively restored. Clear-felling of the conifer trees is often a straight-forward first step, but recent guidance on restoration advocates gradual removal of the plantation crop to protect vulnerable woodland specialist plants. To date there has been little empirical evidence to support this policy. One hundred and four stands in 39 woodland sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
0
18
4
Order By: Relevance
“…There was no indication that the richness of Woodland specialists, as defined by , were adversely affected by opening the canopy in contrast to the findings of Brown et al (2015). The latter used a different definition of specialist plant but at Salcey their species, as a group, tended to do slightly better (and certainly no worse) than either the flora as a whole or Woodland specialists as defined in this study ( Supplementary Table S.1).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…There was no indication that the richness of Woodland specialists, as defined by , were adversely affected by opening the canopy in contrast to the findings of Brown et al (2015). The latter used a different definition of specialist plant but at Salcey their species, as a group, tended to do slightly better (and certainly no worse) than either the flora as a whole or Woodland specialists as defined in this study ( Supplementary Table S.1).…”
Section: Discussioncontrasting
confidence: 59%
“…Plant Strategy Types (Grime et al, 2007) were also noted ( Supplementary Table S1) but no clear patterns emerged with respect to these. Brown et al (2015) used a different definition of specialist plants, although in terms of the species found in Salcey Forest most of their species are also in the Woodland specialist list ( Supplementary Table S1).…”
Section: Data Analyses Changes In Species Occurrence Across the Two Smentioning
confidence: 99%
See 1 more Smart Citation
“…Specific guidelines for restoration of sites previously occupied by planted forests of R. pseudoacacia have been produced in the Piedmont region of Italy and in China (Zhang et al 2018). Sturgess and Atkinson (1993) suggested management strategies for the restoration of near-natural sand dune habitats following the clearfelling of Pinus planted forests in Britain, and Brown et al (2015) proposed approaches for restoring areas previously planted with non-native conifers on ancient woodland sites. Szitár et al (2014) assessed the recovery of open and closed grasslands over five years after the removal of planted forests of non-native pine species through burning in an inland sand dune system in Hungary.…”
Section: Recommendation 6: Design and Adopt Tailored Practices For Inmentioning
confidence: 99%
“…Shukla et al (2014) reported that Shannon-Wiener index of a reserve forest in eastern Himalayas in India was 4.77. Brown et al (2015) reported that clear-felling created a 리 ush of vigorous plant growth, this was not long-lasting, and the end result was reduced plant biodiversity.…”
Section: Vegetation Parametersmentioning
confidence: 99%